Influence of alkali concentration, electric waveform, and frequency on the critical electric field strength of droplet–interface partial coalescence. (23rd November 2019) - Sun, Yongxiang; Yang, Donghai; He, Limin; Luo, Xiaoming; Lü, Yuling
Graphical abstract: Highlights: Alkali used in ASP flooding has impact on droplet–interface electrocoalescence. Elevated water conductivities by adding Na2 CO3 would inhibit partial coalescence. Increased Na2 CO3 solution concentrations retard the penetration of vortex ring. Application of electric fields with different waveforms affects coalescence. The optimal waveform inhibiting partial coalescence changes with frequency. Abstract: During the process of electro-dehydration, the electric field strength should be set below a critical value ( E crit ) to inhibit droplet–interface partial coalescence. The alkali present in alkaline–surfactant–polymer flooding may affect E crit because they change the electrical properties of produced liquids. In view of this, this study investigated the effects of Na2 CO3 solution concentration, electric field waveform, and frequency on the root mean square (RMS) values of E crit . The results show that elevated Na2 CO3 concentrations increase E crit, owing to the enhanced solution conductivity which may affect the charge transfer during coalescence. The convection of ions is associated with penetration of fluid into the bulk phase and an increase in Na2 CO3 concentration decreases the penetration velocity. Moreover, increasing the AC or pulsed electric field frequency can increase E crit, and the optimal waveform (i.e., with the largest E crit ) varies with frequency. These findings will be useful for optimizing electro-coalescence systems.